Carbon storage potential of windbreaks in the United States - Ballesteros-Possú, William; Brandle, James R.; Ordóñez, Héctor Ramiro (Revista de Ciencias Agrícolas, 2019)
In the United States of America, agriculture is performed on large farms of monocultures, affecting ecosystems and making a great contribution to climate change. The carbon storage potential for twelve field windbreak designs containing one-, two- and three-rows and nine farmstead windbreaks encompassing three- to ten-rows of mixed tree species were analyzed in nine regions: Northern Lake States (NLS), Corn Belt (CB), Southern Plains (SP), Delta States (DS), Appalachia (AP), Rocky Mountains North (RMN), Rocky Mountains South (RMS), North East (NE), y Northern Plains (NP), using the US Forest Inventory and Analysis database and allometric equations. Carbon storage potentials for different field windbreak designs across regions ranged from 0.3 Mg C km-1 yr-1 for a single-row small-conifer windbreak in the Northeast region to 5.8 Mg C km-1 yr-1 for a three-row tall-deciduous windbreak in the Appalachia region. Carbon storage potentials for farmstead windbreaks ranged from 0.8 Mg C 300 m-1 yr-1 for a three-row of mixed tree species windbreak in the Rocky Mountain North to 12.7 Mg C 300-1 yr-1 for a ten-row of mixed tree species windbreak in Delta States region.